Thymic Stromal Lymphopoietin and Cancer: Th2-Dependent and -Independent Mechanisms - Protti, Maria P.; De Monte, Lucia (Frontiers in Immunology, 2020)
The thymic stromal lymphopoietin (TSLP) is an IL-7-like cytokine originally cloned from a murine thymic stromal cell line and subsequently a human homolog was identified using database search methods. Human TSLP is mostly expressed in epithelial cells, among which keratinocytes, as well as stromal cells such as fibroblasts, and immune cells. Human TSLP was firstly described to activate myeloid dendritic cells, which prime naïve T helper cells to produce high concentrations of Th2 cytokines, thus representing a key cytokine in triggering dendritic cells-mediated allergic Th2 inflammation. TSLP and/or its receptor has been shown to be expressed in several tumor types, where TSLP expression is associated with functional activities that can be associated or not with the induction of a Th2-prone tumor microenvironment, i.e., Th2-dependent and Th2-independent mechanisms. These mechanisms involve tissue- and immune cell target-dependent tumor-promoting or tumor-suppressive functions in different or even the same tumor type. Here we report and discuss the Th2-dependent and Th2-independent roles of TSLP in cancer and possible therapeutic targeting.